A Review of Role of AI in KriyaSharir - Amruta Suresh Jaybhay (Ayurline: International Journal of Research in Indian Medicine, 2025)
Artificial Intelligence (AI) plays a significant role in Kriyasharir which is the ayurvedic study of human physiology.AI refers to the simulation of Human Intelligence processes in machines which is enabling them to perform tasks that typically require human intelligence such as learning, reasoning, problem solving, interpritting and analysing. The Integration of AI that is Artificial Intelligence into Ayurvedic physiology represents a transformative advancement in the field of traditional Indian medicine. AI brings new possibilities to enhance diagnostic accuracy, innovative tools such as AI-based diagnostic applications, wearable health monitoring devices are increasingly being employed to analyze Ayurvedic parameters of kriyasharir such as Prakriti (body constitution) and dosha (bio-energetic forces)1. AI is useful for the Medical students to understand the basic knowledge of Kriyasharir very easily and apply it with the perfect techniques. Nadi Parikshana also perform with the help of AI.